Accumulation of floating microplastics behind the Three Gorges Dam. (September 2015) - Zhang, Kai; Gong, Wen; Lv, Jizhong; Xiong, Xiong; Wu, Chenxi
Abstract: We investigated the occurrence and distribution of microplastics in surface water from the Three Gorges Reservoir. Nine samples were collected via trawl sampling with a 112 μm mesh net. The abundances of microplastics were from 3407.7 × 10 3 to 13, 617.5 × 10 3 items per square kilometer in the main stream of the Yangtze River and from 192.5 × 10 3 to 11, 889.7 × 10 3 items per square kilometer in the estuarine areas of four tributaries. The abundance of microplastics in the main stream of the Yangtze River generally increased as moving closer to the Three Gorges Dam. The microplastics are made exclusively of polyethylene (PE), polypropylene (PP), and polystyrene (PS). Together with microplastics, high abundance of coal/fly ash was also observed in the surface water samples. Comparing with previously reported data, microplastics in the TGR were approximately one to three orders of magnitudes greater, suggesting reservoirs as potential hot spot for microplastic pollution. Highlights: Occurrence of microplastics was studied in surface water from the Three Gorges Reservoir. Microplastics were identified as polyethylene, polypropylene, and polystyrene. Abundance of microplastics was considerably higher than previously reported data. Abstract : Microplastics were observed in high abundance in surface water from the Three Gorges Reservoir implying reservoirs as structural controls where microplastics accumulate.